Development and Validation of an HPLC-UV Assay for the Therapeutic Monitoring of the New Antiepileptic Drug Perampanel in Human Plasma. Issue 6 (December 2016) - Franco, Valentina; Marchiselli, Roberto; Fattore, Cinzia; Tartara, Elena; De Sarro, Giovambattista; Russo, Emilio; Perucca, Emilio
Abstract : Background: Perampanel, a new specific non-competitive α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor antagonist, has been recently approved in the United States and the European Union for the adjunctive treatment of focal seizures and primary generalized tonic–clonic seizures associated with idiopathic generalized epilepsy. A positive relationship between plasma perampanel concentration and improvement in seizure control has been identified in regulatory trials, suggesting that therapeutic drug monitoring could be useful in optimizing clinical response in patients with epilepsy treated with perampanel. The development of a simple and broadly applicable method for measuring plasma perampanel concentrations is desirable to permit the use of TDM for this drug in clinical practice. Methods: A high-performance liquid chromatographic method with ultraviolet detection for the quantitative determination of perampanel in small aliquots of human plasma (200 μL) has been developed and validated. Sample preparation involves a simple precipitation step followed by solvent evaporation. High-performance liquid chromatographic separation is achieved on 2 reverse-phase monolithic columns in sequence connected to an ultraviolet detector (320 nm), using as mobile phase water/acetonitrile (60:40 vol/vol) mixed with 1 mL/L phosphoric acid, at a flow rate of 1.5 mL/min. Promethazine hydrochloride is used as internal standard. Results: Calibration curves were linear over a perampanel concentration range of 25–1000 ng/mL, with correlation coefficients equal or greater than 0.998 ± 0.001 and a limit of quantitation set at 25 ng/mL. Intra- and inter-day coefficients of variation did not exceed 7.4%, and the accuracy ranged from 96.4% to 113.3%. No interference was observed from commonly coprescribed drugs. Conclusions: The present assay is simple, specific, and cost effective with performance characteristics suitable for TDM use.